2011
DOI: 10.1007/s11746-011-1771-6
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Some Physicochemical Properties and Fatty Acid Composition of Native Black Mulberry (Morus nigra L.) Seed Oil

Abstract: The physicochemical properties of seed and seed oil obtained from the native black mulberry (Morus nigra L.) were investigated in 2008 and 2009. The results showed that the seed consisted of 27.5-33% crude oil, 20.2-22.5% crude protein, 3.5-6% ash, 42.4-46.6% carbohydrate and 112.2-152.0 mg total phenolics/100 g. Twenty different fatty acids were determined, with the percentages varying from 0.02% myristic acid (C14:0) to 78.7% linoleic acid (C18:2). According to the GC analysis of fatty acid methyl esters, li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
17
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 27 publications
11
17
4
Order By: Relevance
“…The linolenic acid (C18:3) ranged from 1.42% (MN4) to 2.40% (MA3). Gecgel et al (2011) found lower levels of linolenic (0.45%) in M. nigra than those found in the current study, whereas Ercisli and Orhan (2007) did not detect it in M. nigra and M. alba.…”
Section: Fatty Acid Composition Of Mulberry Fruitscontrasting
confidence: 96%
See 4 more Smart Citations
“…The linolenic acid (C18:3) ranged from 1.42% (MN4) to 2.40% (MA3). Gecgel et al (2011) found lower levels of linolenic (0.45%) in M. nigra than those found in the current study, whereas Ercisli and Orhan (2007) did not detect it in M. nigra and M. alba.…”
Section: Fatty Acid Composition Of Mulberry Fruitscontrasting
confidence: 96%
“…These results agree with those previously found by Gecgel et al (2011), who reported an average content of 73.70% (C18:2) in black mulberry (M. nigra L.), and also with Yang et al (2010) who observed an average of 79.37% (C18:2) in M. alba L. Among the studied clones, M. nigra had the lowest C18:2 levels (average 72.97%), whereas M. alba clones had the highest levels of this fatty acid (average 74.90%). However, Ercisli and Orhan (2007) in Turkish mulberry fruits found that M. nigra had higher C18:2 levels (average 61.85%) than M. alba clones (average 57.26%).…”
Section: Fatty Acid Composition Of Mulberry Fruitssupporting
confidence: 94%
See 3 more Smart Citations